2020
DOI: 10.1007/s10311-020-01063-0
|View full text |Cite
|
Sign up to set email alerts
|

Lower COVID-19 mortality in Italian forested areas suggests immunoprotection by Mediterranean plants

Abstract: The COVID-19 pandemic has induced dramatic effects on the population of the industrialized north of Italy, whereas it has not heavily affected inhabitants of the southern regions. This might be explained in part by human exposure to high levels of fine particulate matter (PM) in the air of northern Italy, thus exacerbating the mortality. Since trees mitigate air pollution by intercepting PM onto plant surfaces and bolster the human immune system by emitting bioactive volatile organic compounds (VOCs), we hypot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
70
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(73 citation statements)
references
References 91 publications
2
70
0
1
Order By: Relevance
“…Air pollution also acts as the route for much other secondary diseases and associated deaths (Walker 2020). Lower COVID-19 mortality in forested areas reinforces the influence of air pollution and suggests immunoprotection by Mediterranean plants (Roviello and Roviello 2020). Death rates under air pollution-related diseases and associated complications are at least 100-folds more in poor countries in comparison to the countries with high income.…”
Section: Air Pollution and Covid-19 Severitymentioning
confidence: 94%
“…Air pollution also acts as the route for much other secondary diseases and associated deaths (Walker 2020). Lower COVID-19 mortality in forested areas reinforces the influence of air pollution and suggests immunoprotection by Mediterranean plants (Roviello and Roviello 2020). Death rates under air pollution-related diseases and associated complications are at least 100-folds more in poor countries in comparison to the countries with high income.…”
Section: Air Pollution and Covid-19 Severitymentioning
confidence: 94%
“…Further, recent studies indicated that high concentrations of aerosol particles could significantly increase the susceptibility of COVID-19 infection and symptom aggravation in infected individuals (Accarino et al 2020 ; Fattorini et al 2020 ; Roviello et al 2020 ; Travaglio et al 2020 ). A known contributing factor is that airborne particles are capable of harboring pathogens by forming clusters with droplets and droplet nuclei and facilitate their long-distance transport (Alonso et al 2014 ; Zhao et al 2019 ).…”
Section: Transmission Of Covid-19 By Virus-laden Droplets and Indoormentioning
confidence: 99%
“…Before scientists find a perfect cure for treating infections by the novel coronavirus, vaccinating the global population will be the keystone in the current battle against COVID-19 (Stern 2020;Williams et al 2020). The numerous challenges in the lab-to-jab process not only present a daunting task, but also provide an unprecedented opportunity to collaborating and finding innovative solutions, on a global scale and across different disciplines to increase the preparedness of our communities for future pandemics (Paital and Agrawal 2020;Roviello and Roviello 2020;Sharma et al 2020;Wang et al 2020d). Since epidemics and pandemics may emerge in a not too distant future, these experiences will become an important part of the legacy of the COVID-19 era.…”
Section: Mutationsmentioning
confidence: 99%